A novel chaotic encryption scheme based on efficient secret keys and confusion technique for confidential of DICOM images. (2020) - Mortajez, Sareh; Tahmasbi, Marziyeh; Zarei, Javad; Jamshidnezhad, Amir
Abstract: This paper proposed a secure encryption scheme based on the chaotic system and periodic confusion strategy with dynamic secret keys to protect medical images. The proposed scheme can be applied to DICOM standard images which are generally employed in medical systems and applications. Firstly, secret keys are extract from the pixels' information of the medical image. Then, the positions of pixels are permuted based on periodic confusion strategy and pseudo-random sequences. Finally, permuted image pixels are coded based on sequences of logistic systems and the XOR operator. The performance of the presented encryption scheme was evaluated by several security analyses. The results assure the efficiency of the proposed schema, the NPCR and UACI are improved over 99.6% and 33.5% respectively, and entropy is reported close to 7.9994. The comparison with similar DICOM encryption algorithms is made. The analysis results confirm that our proposed encryption scheme meets the security requirements of medical images encryption and is capable of resisting the main cryptographic attacks.